Brazilian sign language: Inclusion of the deaf in university education at Instituto Federal Paraná (IFPR) Campus Curitiba (Research, Society and Development, 2023)
We understand that deafness, many times, is related to linguistic and interactional limitations loaded with prejudice for those who have it. Some linguistic barriers prevent deaf people to a full life and a quality education. The objective of this article is to present a small glimpse regarding the trajectory of the deaf and their struggles, using as a basis the laws and data from the Federal Institute of Parana (IFPR) Curitiba Campus in the Center for Support to People with Specific Needs (NAPNE). Official documents of the Federal Institute of Paraná Curitiba Campus were analyzed, along with the Law No. 10.436 of April 24, 2002, and regulated by Decree No. 5.626 of December 22, 2005 ensuring accessibility of the deaf in the education system, according to Law No. 13.146 of July 6, 2015 which establishes the inclusion of people with disabilities. Based on the doctrines and relevant legislation to the subject and to reach the conclusion of how the applicability of laws and doctrines to the concrete case. We conclude with the research that the inclusion and accessibility in higher education have not been happening in a full way, because there is still a struggle to have a real inclusion that has special needs in higher education in the Federal Institute of Parana (IFPR) that still lacks adequate linguistic accessibility to the deaf.